2012
DOI: 10.1007/s00330-012-2447-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure and mortality risk from CT and PET imaging of patients with malignant lymphoma

Abstract: ObjectiveTo quantify radiation exposure and mortality risk from computed tomography (CT) and positron emission tomography (PET) imaging with 18F-fluorodeoxyglucose (18F-FDG) in patients with malignant lymphoma (Hodgkin’s disease [HD] or non-Hodgkin’s lymphoma [NHL]).MethodsFirst, organ doses were assessed for a typical diagnostic work-up in children with HD and adults with NHL. Subsequently, life tables were constructed for assessment of radiation risks, also taking into account the disease-related mortality.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 35 publications
1
51
0
4
Order By: Relevance
“…Several recent studies have demonstrated that routine follow-up by 18 F-FDG PET/CT and other imaging techniques may be overused for routine surveillance of patients with HL, contributing to increased cost and radiation exposure without a clear survival benefit (6,50,58). More data are needed to determine which patient group will benefit from which surveillance test for how long and at which frequency.…”
Section: Therapy Response Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have demonstrated that routine follow-up by 18 F-FDG PET/CT and other imaging techniques may be overused for routine surveillance of patients with HL, contributing to increased cost and radiation exposure without a clear survival benefit (6,50,58). More data are needed to determine which patient group will benefit from which surveillance test for how long and at which frequency.…”
Section: Therapy Response Assessmentmentioning
confidence: 99%
“…Several studies have demonstrated improved sensitivities and specificities for 18 F-FDG PET/CT compared with all collective standard staging procedures, specifically for patients with lymphomas, sarcomas, and head and neck cancers (1)(2)(3)(4). However, exposure of children to radiation through 18 F-FDG PET/CT is of concern to the pediatric imaging community (5,6), and various low-dose approaches are being pursued (7)(8)(9). A thorough understanding of the state of knowledge is needed to preserve the advantages of current 18 F-FDG PET/CT staging tests and create new imaging tests without compromises.…”
mentioning
confidence: 99%
“…With the recommendation of frequent PET/CT however, there is significant accumulation of radiation over time, which raises concerns specifically in young patient populations [65]. The expected benefit of PET/MRI in this regard appears obvious in that radiation exposure can be limited to the dose generated by the radioactive tracer.…”
Section: Lymphomamentioning
confidence: 99%
“…In some countries nuclear medicine is an independent specialty, and in other countries radiologists are in charge of nuclear medicine tests. Physicians-in-training in radiology and in nuclear medicine have to receive multimodality training [8][9][10][11][12]. And continuing education in both specialties is vital to ensure that senior specialists are well-versed in the latest techniques.…”
mentioning
confidence: 99%
“…The most typical example is abdominal CT, which has a higher dose than the most frequent nuclear medicine studies. Another example is that two-thirds of the radiation dose from PET/CT is from the CT component [12][13][14]. In the latter case it is possible to perform a diagnostic CT scan during the PET/CT examination rather than a separate diagnostic CT scan.…”
mentioning
confidence: 99%